(untitled) (Research, Society and Development, 2022)
Faced with concerns when reading texts produced by authors with different levels of education and finding gross mistakes in the use of punctuation marks, especially in the inappropriate use of the comma that can compromise communication, this work proposes a didactic sequence for teaching the use. of the comma, as an element of textual production, which obeys syntactic criteria. The proposal should be adopted for students from elementary school – final years, after the basic learning of syntactic structures. A bibliographical research with a qualitative approach was carried out on punctuation, comma and didactic sequence, in order to support the proposal presented. Reflections were provided by researchers such as: Ferrarezi Junior (2019), Junkes (1995), Kleiman (2016), Koch and Elias (2015), Luft (2002), Piacentini (2012), Oliveira (2019), among others. Through the discussions carried out, it is expected that the proposed pedagogical practice can contribute to teaching the use of comma consciously, enhancing writing skills and possibilities for better textual comprehension.